Developing an intersectional consciousness and praxis : moving toward antiracist efforts in higher education - McElderry, Jonathan; Hernandez, Stephanie (Identity & practice in higher education-student affairs., 2025)
"Colleges and universities across the country continue to struggle supporting students with marginalized identities, including (but not limited to) gender, race, ethnicity, sexual identity, ability level, socio-economic status, religious identity, and citizenship status. The creation of safe and inclusive learning environments necessitates the adoption of equitable policies and practices (McElderry & Hernandez-Rivera, 2019). Therefore, this book can be used as a tool for practitioners to further support students from marginalized identities at PWIs. Grounded in the NASPA/ACPA Core Competencies, this book allows practitioners to share their knowledge and best practices in how they support students of color across the following functional areas in higher education: Student Learning & Development; Social Justice & Inclusion; Health & Wellbeing; Advising & Supporting; Assessment, Evaluation, & Research; Senior/Executive Leadership"--